Analisis Risk Priority Number Cacat Produk Cup Air Mineral dengan Pendekatan Seven Tools Di PT. XYZ - Misbachul Munir (Universitas Yudharta Pasuruan, 2021)
Abstract PT. XYZ is a company engaged in producing bottled drinking water. To compete in the market, it is demanded to maintain the quality of the goods produced because of the quality products so that it has the aim of knowing the causes of significant product defects in the 240 ml cup packaging at PT. XYZ and knowing what factors cause defects in 240 ml cup packaging products at PT. XYZ Abstract is written in Indonesian as well as using the seven tools method. The results show that the cause of product defects is based on the cause and effect diagram of lid defects including: 1) leaking lid: Heater is not hot enough, heater is too hot, bucket with trimming is not center, seal disk is dirty and operators are less careful. 2) Broken lid: The lid is brittle and the handling is not good 3) Tilted lid: The position of the roll lid shakes and the operator is not careful. Keywords: Quality, product defects, Seven Tools Abstrak XYZ merupakan perusahaan yang bergerak di bidang memproduksi air minum dalam kemasan. Untuk bersaing di pasaran maka di tuntut untuk menjaga kualitas dari barang yang di hasilkan karena produk yang berkualitas sehingga memiliki tujuan untuk mengetahui penyebab kecacat produk yang signifikan pada kemasan cup 240 ml di PT. XYZ dan mengetahui Faktor-faktor apa yang menjadi penyebab ke cacat produk kemasan cup 240 ml di PT. XYZ Abstrak ditulis dalam Bahasa Indonesia segingga dengan menggunakan metode seven tools di dapatkan hasil bahwa Penyebab terjadinya kecacatan produk berdasarkan diagram sebab akibat cacat lid diantaranya: 1) bocor lid : Heater kurang Panas, heater terlalu panas, bucket dengan trimming tidak center, seal disk kotor dan operator kurang cermat. 2) Pecah lid : Lid getas dan handling kurang baik 3) Lid Miring : Kedudukan roll lid goyang dan operator kurang teliti. Kata Kunci: Kualitas, cacat produk, Seven Tools